PARTICIPATORY LEARNING BASED ON ENTREPRENEURSHIP IN INDEPENDENT WOMEN'S GROUPS - Ansori; Arianti Handayani , Farida; Hasbi Noor, Agus (Journal Of Educational Experts (JEE), 2025)
Empowering women through entrepreneurship-based education is a strategic effort to enhance the economic independence of independent women's groups. This study aims to develop a participatory learning model based on entrepreneurship to support the skill enhancement and capacity building of women’s groups at PKBM An Nur. This research employed a qualitative approach with a participatory action research (PAR) design. Data were collected through in-depth interviews, observations, and document studies involving participants and learning facilitators. The findings reveal that the participatory entrepreneurship-based learning model effectively increased active participation, facilitated the development of independent businesses, and strengthened social networks. The model's success lies in its collaborative approach, local relevance, and hands-on practice. This study offers a novel contribution by integrating participatory approaches with entrepreneurial concepts as an innovative solution for women's empowerment. In conclusion, this model has the potential to serve as a reference for other community education institutions in supporting women’s economic independence in the era of Society 5.0. Keywords: Participatory Learning, Entrepreneurship, Women Empowerment